Developing a multidimensional scale for presenteeism: A study on measurement and implications - Mumlu-Karanfil, S.; Dogan, A.; Bozkurt, S. (URAL STATE UNIV ECONOMICS, 2024)
Presenteeism is among the key factors that negatively affect employee efficiency and, therefore, company organizational performance. The existing measurement tools for assessing presenteeism highlight health-related issues as the main reason behind this counterproductive behaviour. On the other hand, other factors that influence modern business life and processes are omitted.The paper's primary purpose is to develop a comprehensive measurement tool suitable for the individual and organizational multi-factor structure of presenteeism that accurately reflects the complex nature of today's business world. Methodologically, the research is shaped within the framework of grounded theory. In the study, mixed methods research combining qualitative and quantitative methods was utilized. In this context, firstly, the authors conducted a literature review and focus group interviews with experts in the field in order to reveal the conceptual structure. We analysed the data using content analysis and then moved on to writing 18 scale items. We performed exploratory factor analysis using the SPSS program and confirmatory factor analysis using the AMOS program. As a result, we develop a four-dimensional scale for presenteeism covering work focus, stress management, social loafing, and performance. The verified multidimensional scale fills a vacuum in the literature by offering a comprehensive and dependable instrument to gauge presenteeism on organizational and individual dimensions. Among the possible avenues for further research are testing the scale in different cultural contexts and addressing the organizational causes of presenteeism.
Keywords: presenteeism; absenteeism; productivity; presenteeism assessment; multidimensional scale; Turkey; HEALTH CONDITIONS; SICKNESS PRESENTEEISM; WORK-ENVIRONMENT; ABSENCE; IMPACT; COST; ILL; PERFORMANCE; DISABILITY; Business & Economics